Study of Green Architecture in Slum Settlements at Belawan Harbor City - Novalinda; Dara Wisdianti; Ardiansyah (Yayasan Sinergi Multidimensi Kreatif, 2024)
The Bagan Deli Sub-district settlement in Belawan Harbor city is a densely populated settlement. The dense population is not evenly distributed but at certain points only. The condition of this settlement has a lowland with an altitude of 1 (one) meter above sea level. The problems that occur in Bagan Deli are garbage accumulation, tidal flooding, poor drainage systems and lack of awareness of throwing garbage into drainage. Tidal flooding occurs every time so that water enters the house causing the house to become dirty and seem very slum and unhealthy in the Bagan-Deli settlement. The method used by Green Architecture refers to the Building Green Building (BGH) regulation. The goal is to increase the efficiency of energy use, water, and the use of house materials. Green Building related regulations are Number 21 of 2021 concerning Technical Planning Stage Parameters for Green Areas The criteria that become requirements include; improving the welfare of the local population, improving the service function of infrastructure and facilities in the area, controlling the microclimate and preserving the ecosystem in the area, reducing the thermal impact on other areas in the dry season, reducing the burden on infrastructure and facilities, using environmentally friendly materials.